Broadly tunable photon-pair generation in a suspended-core fiber - Hammer, Jonas; Chekhova, Maria; Häupl, Daniel; Pennetta, Riccardo; Joly, Nicolas (Physical Review Research, 2020)
Nowadays fiber biphoton sources are nearly as popular as crystal-based ones. They offer a single spatial mode and easy integrability into optical networks. However, fiber sources lack the broad tunability of crystals, which do not require a tunable pump. Here, we report a broadly tunable biphoton source based on a suspended core fiber. This is achieved by introducing pressurized gas into the fibers hollow channels, changing the step index. The mechanism circumvents the need for a tunable pump laser, making this a broadly tunable fiber biphoton source with a convenient tuning mechanism, comparable to crystals. We report a continuous shift of 0.30 THz/bar of the sidebands, using up to 25 bar of argon.
CRIS-Team WoS Importer:2021-01-15

Spatially resolved spectroscopy of alkali metal vapour diffusing inside hollow-core photonic crystal fibres - Häupl, Daniel; Weller, Daniel; Loew, Robert; Joly, Nicolas (New Journal of Physics, 2022)
We present a new type of compact and all-glass based vapour cell integrating hollow-core photonic crystal fibres. The absence of metals, as in a traditional vacuum chamber and the much more compact geometry allows for fast and homogeneous heating. As a consequence we can fill the fibres on much faster timescales, ranging from minutes to hours. Additionally the all-glass design ensures optical access along the fibre. This allows live monitoring of the diffusion of rubidium atoms inside the hollow-core by measuring the frequency-dependent fluorescence from the atoms. The atomic density is numerically retrieved using a five-level system of Bloch-equations.
CRIS-Team WoS Importer:2022-11-25